The Turkish-Israeli strategic co-operation and mediterranean security - Özdemir, Aşkın Berk (My University, 2002)
Bu çalışmanın amacı Türkiye ve İsrail ikili ilişkileri çerçevesinde gerçekleşen stratejik işbirliğinin dinamiklerini açıklamak ve işbirliğinin Akdeniz Güvenliği üzerinde yaptığı etkileri incelemektir. Çalışma genel hatlarıyla iki ana bölümden oluşmaktadır. venlik teriminin genel anlamı, uluslararası ilişkilerdeki yeri ve terimin tarihten günümüze doğru değişen uluslararası sistemler doğrultusunda evrimi hakkında genel ve açık bilgilerle başlamaktadır. Devam eden safhada Akdeniz bölgesinin bu çalışma çerçevesinde tercih edilen tanımı ve konsepti verilmekte ve bölgenin Soğuk Savaş ve Soğuk Savaş Sonrası dönemlerdeki statüsü karşılaştırılmaktadır. Akdeniz bölgesinde görülen problemler ve bölgenin dünyanın önde gelen aktörleri açısından önemi belirtildikten sonra stratejik işbirliğinin etkilerinin görüldüğü ana alt bölge olan Doğu Akdeniz ile ilgili bilgilerle sona ermektedir. İkinci bölüm, işbirliğinin önünü açan faktörler ve ortakların işbirliğinden beklentilerle başlamaktadır. Ayrıca işbirliğinin safhaları kronolojik bir sırada anlatılmaktadır. Bir ileri safhada işbirliğinin bölge güvenliği üzerindeki, olumlu ya da olumsuz etkileri açıklanmakta ve bu çerçevede işbirliğine bölgeden gelen tepkilere ve Amerika' nın gelişmelerdeki rolüne yer verilmektedir. Çalışma, son gelişmeler ışığında, işbirliğinin geleceği ve Akdeniz Güvenliği'nin evrimi ile ilgili düşüncelerle sonuçlanmaktadır. This study seeks to analyze the dynamics of the strategic co-operation between Turkey and Israel and the impact of the co-operation on the security of the Mediterranean region. It has mainly composed of two parts. The first part begins with a brief theoretical explanation of the concept 'security'. Explanatory answer are given to the questions such as what is security, how has the term been perceived in international relations over the years? After dealing with concept 'security', the following part focuses on the specifics of the Mediterranean region and makes a comparative analysis of the status of Mediterranean during the period of the Cold War and the Post-Cold War era. Chapter 3 examines the Eastern Mediterranean as a sub-region because the impact of the Turkish-Israeli strategic co-operation was most evident in this part of Mediterranean. The following chapter is devoted to the Turkish-Israeli strategic co-operation and its effects on the parties involved and the security of Mediterranean in general. In addition to a chronological evolution of the bilateral relations the factors that led to the co-operation and the motivations of each part are discussed. Finally the effects of the strategic co-operation on the Mediterranean security in general and on the Eastern Mediterranean security in particular are being elaborated. In this framework it is important to show what the implications of the Turkish-Israeli strategic co-operation were on regional security both positively and negatively and how the other regional countries and America responded to this co-operation. The study is concluded with thoughts on the future of the co-operation and the evolution of the security in the Mediterranean in the light of the recent events, especially of the September 11th attack.
Keywords: İsrail_Uluslararası İlişkiler_Türkiye; Kültürler arasındaki temaslar; Toplumsal değişim; Türkiye_Uluslararası İlişkiler_İsrail